Cultural Diversity in International Business : The Spanish-Moroccan Business Context - Anca, Celia de; Durán, Irene; El Hachami, Noureddine; Anca, Celia de (IE Fundation, 2019)
The IE Center for Diversity, in collaboration with the ONA Foundation and the support of Averroes Committee and the Spanish Agency for International Cooperation (AECI), has published a best practices guide to integrating diversity into HR management, providing guidance for Spanish companies operating in Morocco and Moroccan companies working in Spain.
Keywords: International business; Spain; Morocco; Global management; Economy